2018
DOI: 10.1002/jsfa.9265
|View full text |Cite
|
Sign up to set email alerts
|

Changes in secondary metabolites, organic acids and soluble sugars during the development of plum fruit cv. ‘Furongli’ (Prunus salicina Lindl)

Abstract: Dynamics in organic acid anions were not solely controlled by a single enzyme but regulated by the integrated activity of enzymes such as nicotinamide adenine dinucleotide phosphate-malic enzyme (NADP-ME), NAD-ME, PEPC, ACO and NADP-isocitrate dehydrogenase. Sugar metabolism enzymes such as PGI, invertase and HK may play vital roles in the regulation of individual sugar metabolic processes. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 50 publications
(105 reference statements)
5
41
1
1
Order By: Relevance
“…, while Díaz-Mula et al. (2008) described a decrease in phenolics over development of plum; Jiang et al. (2019) showed an increase of phenolic compounds.…”
Section: Pre- and Postharvest Treatments Affecting The Phytochemical mentioning
confidence: 97%
See 1 more Smart Citation
“…, while Díaz-Mula et al. (2008) described a decrease in phenolics over development of plum; Jiang et al. (2019) showed an increase of phenolic compounds.…”
Section: Pre- and Postharvest Treatments Affecting The Phytochemical mentioning
confidence: 97%
“…In consequence, the harvest time might affect the health-beneficial properties of the fruit. In this respect, research conducted in plums shows the evolution of the content of different secondary organic metabolites such as carotenoids, total phenolics, anthocyanins during development and ripening on tree of different cultivars ( Díaz-Mula et al., 2008 ; Jiang et al., 2019 ). Nevertheless, these works showed contradictory results i.e.…”
Section: Pre- and Postharvest Treatments Affecting The Phytochemical mentioning
confidence: 99%
“…Only two studies evaluated the changes in contents of these compounds during fruit development, and the results are contradictory. Indeed, one study reported an increase in these compounds throughout fruit development [27], whilst another found a decrease [29]. Therefore, clarification of these differences is required.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies regarding the changes in the contents of both primary and secondary metabolites (carbohydrates, malic acid, and antioxidants) have only investigated in the period up to commercial harvest [1,15,29]. In this study, the contents of these metabolites were determined throughout the entire natural period of fruit growth on the tree (that is, until the drop of the fruits from the tree), and we refer to this previously unstudied extra period as the over–ripening period,…”
Section: Introductionmentioning
confidence: 99%
“…De modo geral, os ácidos orgânicos do ciclo do ácido tricarboxílico tendem a reduzir no estágio final de maturação de frutos, que tem sido sugerido como sendo causado pelo metabolismo básico aumentado e síntese de açúcar ou compostos secundários em frutos maduros (BATISTA-SILVA et al, 2018;BERÜTER, 2004;DURMAZ et al, 2010;ETIENNE et al, 2013;JIANG et al, 2019;LOMBARDO et al, 2011). Rogers et al (1999) relataram que as sementes jovens de café tem alta concentração de ácido quínico e os níveis diminuem à medida que o fruto atinge o estádio final do seu desenvolvimento.…”
Section: Perfil Dos Metabólitos Em Resposta à Carga De Frutosunclassified